Seroepidemiologi Antibodi Anti HIV berdasarkan Karakteristik Demografi pada Pendonor Darah di UDD PMI Kabupaten Probolinggo - Ni'mah, Ana Masfurotin; Prasetyowati, Irma; Bumi, Candra (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: One of the indicators of HIV virus contamination in donor blood is the presence of anti-HIV antibodies. According to Probolinggo Blood Transfusion Unit, there are 55 blood donors screened reactive for anti-HIV antibodies in 2013-2018. Infected Blood by HIV virus causes a risk to donor recipients, especially the transmission of infection through blood transfusions. The purpose of this study is to describe the seroepidemiological trends of anti-HIV antibodies in blood donors. Methods: Descriptive research using annual data from Probolinggo Blood Transfusion Unit. The samples used in this study were all blood donors in 2013-2019 (29,421 blood donors). Blood donors were screened using Murex Ab/Ag Combination Diasorin UK Branch. Data were analyzed using descriptive statistics. Result: There were 0.19% anti-HIV antibodies reactive in the blood of donors with the characteristics of blood donors were males, O blood types, voluntary and recurrent donors and conducting blood donor Kraksaan District. Conclusion: Based on the results of this study, Probolinggo has a relatively low number of anti-HIV antibody findings. Nonetheless, the results show there has been an increase in the results of reactive screening for anti-HIV antibodies over the past 6 years in Probolinggo. Therefore, it is very necessary to maintain the quality of the screening that has been done and coordinate with the Probolinggo DHO to follow up on this problem.